The Psychological Impact of Social Media on the Self-Esteem and Body Image of Pre-Adolescent Students - Budiawan Budiawan; Bruna Costa; Raul Gomez (Yayasan Adra Karima Hubbi, 2025)
The increasing use of social media has raised concerns about its psychological impact on young adolescents, particularly concerning their self-esteem and body image. This study explores the effects of social media engagement on the self-esteem and body image perceptions of pre-adolescent students aged 10-12 years. The research aimed to assess how the frequency and nature of social media use contribute to body dissatisfaction and self-esteem levels among pre-adolescents. A mixed-method approach was employed, using surveys and in-depth interviews with 200 pre-adolescent students from four schools. The quantitative data were analyzed through descriptive statistics and correlation analysis, while qualitative data were thematically analyzed to gain deeper insights into personal experiences. The results indicated a significant negative correlation between social media usage and self-esteem, with increased exposure to idealized body images linked to higher levels of body dissatisfaction. Moreover, participants reported feeling pressure to conform to social media beauty standards, which impacted their body image perceptions. In conclusion, the findings highlight the importance of managing social media exposure for young adolescents to mitigate its potential negative effects on self-esteem and body image. Educational and parental interventions are essential to support pre-adolescents in developing healthier social media habits.